2022
DOI: 10.1186/s13550-022-00896-w
|View full text |Cite
|
Sign up to set email alerts
|

Larger 18F-fluoroboronotyrosine (FBY) active volume beyond MRI contrast enhancement in diffuse gliomas than in circumscribed brain tumors

Abstract: Background To investigate the relationship between 18F-fluoroboronotyrosine (FBY) positron emission tomography (PET)- and magnetic resonance imaging (MRI)-defined tumor volumes in contrast-enhanced diffuse gliomas and circumscribed brain tumors. Methods A total of 16 diffuse gliomas and 7 circumscribed brain tumors were included, and two types of three-dimensional regions of interest (ROIs), namely, MRI-based ROI (ROIMRI) and FBY-based ROI (ROIFBY)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The clinical value of FAPI PET has been proven for differential diagnosis, TNM staging, radiation planning, and treatment response evaluation as a replacement or complementary tool for 18 F-FDG PET and other imaging modalities. Although preliminary studies on FAP-targeted radionuclides reported acceptable safety profiles and mixed responses in certain patients, the relatively fast clearance of FAPIs compared with the half-life of treatment nuclides limits the achievable radiation dose. In preclinical studies, 93% of 225 Ac-FAPI-04 was excreted through urine and feces 24 h after administration, and tumor uptake was 0.3%ID/g at 3 h and 0.1%ID/g at 24 h for 177 Lu-FAPI-46 and 225 Ac-FAPI-46 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical value of FAPI PET has been proven for differential diagnosis, TNM staging, radiation planning, and treatment response evaluation as a replacement or complementary tool for 18 F-FDG PET and other imaging modalities. Although preliminary studies on FAP-targeted radionuclides reported acceptable safety profiles and mixed responses in certain patients, the relatively fast clearance of FAPIs compared with the half-life of treatment nuclides limits the achievable radiation dose. In preclinical studies, 93% of 225 Ac-FAPI-04 was excreted through urine and feces 24 h after administration, and tumor uptake was 0.3%ID/g at 3 h and 0.1%ID/g at 24 h for 177 Lu-FAPI-46 and 225 Ac-FAPI-46 .…”
Section: Discussionmentioning
confidence: 99%
“…5D). 48,50,51 The studies demonstrated that BAAs are biocompatible, rapidly cleared in normal tissue, and leave no residue in the body, thus laying a solid foundation for their use as bioorthogonal reaction activators. The clearly defined pharmacokinetics facilitates optimal timing and dosing of the activator and prodrug administration.…”
Section: Desilylation For Drug Releasementioning
confidence: 99%
“…80 FBY shows promise in assessing brain tumors, and its metabolism has been found to be significantly increased in most neoplasms, whereas it remained low in non-cancerous lesions. 79,80 In comparison to other amino acid PET tracers, like FET and 4borono-2-18 F-fluorophenylalanine (FBPA), FBY exhibited reduced background activity, with mean and maximum SUV values of 0.037 and 0.116, respectively, allowing a clearer visualization of tumors, and may help in identifying small lesions and defining treatment targets. 80 Preclinical and clinical studies show that the energyindependent LAT-1 system preferentially takes up 99m Tcmethionine, referring to 99m Tc-DTPA-bis(Met) in tumor cells.…”
Section: Modalities In Nuclear Medicinementioning
confidence: 99%
“…79,80 In comparison to other amino acid PET tracers, like FET and 4borono-2-18 F-fluorophenylalanine (FBPA), FBY exhibited reduced background activity, with mean and maximum SUV values of 0.037 and 0.116, respectively, allowing a clearer visualization of tumors, and may help in identifying small lesions and defining treatment targets. 80 Preclinical and clinical studies show that the energyindependent LAT-1 system preferentially takes up 99m Tcmethionine, referring to 99m Tc-DTPA-bis(Met) in tumor cells. In a preliminary study, it localizes selectively in recurrent/ residual gliomas and has excellent target-to-non-target (T/NT) image contrast.…”
Section: Modalities In Nuclear Medicinementioning
confidence: 99%
See 1 more Smart Citation